1935
DOI: 10.1002/cber.19350681233
|View full text |Cite
|
Sign up to set email alerts
|

Über hochpolymere Verbindungen, 127. Mitteil.: Über osmotische Bestimmungen an Lösungen mit stab‐ und kugelförmigen Teilchen

Abstract: Staudinger, Schulz: [Jahrg. 68 456. H. Staudinger und G. V. Schulz: tfber hochpolymere Verbindungen, 127. Mitteil. 1) : tfber osmotische Bestimmungen an Losungen mit stab-und kugelformigen Teilchen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1936
1936
1939
1939

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been widely supposed that the rate of polymerization of vinyl compounds is conditioned by the rate at which the catalyst first reacts with the monomer to give rise to active centres, and it has been considered that the subsequent process involving the building up of the polymer from the monomer takes place extremely rapidly and does not constitute a limiting factor. The basis for this viewpoint has largely been founded upon the experiments of Staudinger and Frost (1935) and of Schulz and Husemann (*936)5 who determined the molecular weight of the polystyrene formed at different stages in the process of polymerization and found that it was independent of the percentage polymerization. (See also Stobbe and Posnjak 1909;Stobbe and Lippold 1914;Lebedev and Mereshkowski 1913.…”
mentioning
confidence: 99%
“…It has been widely supposed that the rate of polymerization of vinyl compounds is conditioned by the rate at which the catalyst first reacts with the monomer to give rise to active centres, and it has been considered that the subsequent process involving the building up of the polymer from the monomer takes place extremely rapidly and does not constitute a limiting factor. The basis for this viewpoint has largely been founded upon the experiments of Staudinger and Frost (1935) and of Schulz and Husemann (*936)5 who determined the molecular weight of the polystyrene formed at different stages in the process of polymerization and found that it was independent of the percentage polymerization. (See also Stobbe and Posnjak 1909;Stobbe and Lippold 1914;Lebedev and Mereshkowski 1913.…”
mentioning
confidence: 99%